Comparative Evaluation of MVAC-LVDC SST and Hybrid Transformer Concepts for Future Datacenters - Huber, Jonas; Wallmeier, Peter; Pieper, Ralf; Schafmeister, Frank; Kolar, Johann (Proc. 9th IEEJ International Power Electronics Conference (IPEC))

Quantification of the adhesive coupling of layered structures using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Model of a Self-Sufficient PV Home using a Hybrid Storage System based on Li-Ion Batteries and Hydrogen Storage with Waste Heat Utilization - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
This paper provides a hybrid energy system model created in Matlab/Simulink which is based on photovoltaics as its main energy source. The model includes a hybrid energy storage which consists of a short-term lithium-ion battery and hydrogen as long-term storage to ensure autonomy even during periods of low PV production (e.g., in winter). The sectors heat and electricity are coupled by using the waste-heat generated by production and reconversion of hydrogen through an electrolyser respectively a fuel cell. A heat pump has been considered to cover the residual heat demand (for well insulated homes). Within this paper a model of the space heating system as well as the hot water heating system is presented. The model is designed for the simulation and analysis of a whole year energy flow by using a time series of loads, weather and heat profiles as input. Moreover, results of the energy balance within the energy system by simulation of a complete year by varying the orientation (elevation and azimuth) of the PV system and the component sizing, such as the lithium-ion battery capacity, are presented. It turned out that a high amount of heating energy can be saved by using the waste heat generated by the electrolyser and the fuel cell. The model is well suited for the analysis of the effects of different component dimensionings in a hydrogen-based energy system via the overall energy balance within the residential sector.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.

Visualisierung von Ultraschallfeldern mittels Schlierentechnik und fraktionaler Fouriertransformation - Hetkämper, Tim

Messverfahren für die akustische Absorption zur Bestimmung der Volumenviskosität - Claes, Leander

Schlieren imaging with fractional Fourier transform to visualise ultrasonic fields - Hetkämper, Tim; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme - Beiträge der 21. ITG/GMA-Fachtagung)

Light backscattering from numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens
Keywords: tet_topic_scattering

AI Assisted Interference Classification to Improve EMC Troubleshooting in Electronic System Development - Maalouly, Jad; Hemker, Dennis; Hedayat, Christian; Rückert, Christian; Kaufmann, Ivan; Olbrich, Marcel; Lange, Sven; Mathis, Harald (2022 Kleinheubach Conference)
In this paper, machine learning techniques will be used to classify different PCB layouts given their electromagnetic frequency spectra. These spectra result from a simulated near-field measurement of electric field strengths at different locations. Measured values consist of real and imaginary parts (amplitude and phase) in X, Y and Z directions. Training data was obtained in the time domain by varying transmission line geometries (size, distance and signaling). It was then transformed into the frequency domain and used as deep neural network input. Principal component analysis was applied to reduce the sample dimension. The results show that classifying different designs is possible with high accuracy based on synthetic data. Future work comprises measurements of real, custom-made PCB with varying parameters to adapt the simulation model and also test the neural network. Finally, the trained model could be used to give hints about the error’s cause when overshooting EMC limits.
Keywords: emc; pcb; electronic system development; machine learning; neural network

Microinverter PV Systems: New Efficiency Rankings and Formula for Energy Yield Assessment for any PV Panel Size at different Microinverter types - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 8th World Conference on Photovoltaik Energy Conversion)

Optimal Design of a Semi Grid-Connected PV System for a Site in Lwak, Kenya Using HOMER - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 8th World Conference on Photovoltaik Energy Conversion)

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Model Predictive Torque Control for Permanent Magnet Synchronous Motors Using a Stator-Fixed Harmonic Flux Reference Generator in the Entire Modulation Range - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

The Scale4Edge RISC-V Ecosystem - Ecker, Wolfgang; Adelt, Peer; Müller, Wolfgang; Heckmann, Reinhold; Krstic, Milos; Herdt, Vladimir; Drechsler, Rolf; Angst, Gerhard; Wimmer, Ralf; Mauderer, Andreas; Stahl, Rafael; Emrich, Karsten; et al. (In Proceedings of the Design Automation and Test Conference and Exhibition (DATE 2022))
This paper introduces the project Scale4Edge. The project is focused on enabling an effective RISC-V ecosystem for optimization of edge applications. We describe the basic components of this ecosystem and introduce the envisioned demonstrators, which will be used in their evaluation.

Stress-Aware Periodic Test of Interconnects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing)
Safety-critical systems have to follow extremely high dependability requirements as specified in the standards for automotive, air, and space applications. The required high fault coverage at runtime is usually obtained by a combination of concurrent error detection or correction and periodic tests within rather short time intervals. The concurrent scheme ensures the integrity of computed results while the periodic test has to identify potential aging problems and to prevent any fault accumulation which may invalidate the concurrent error detection mechanism. Such periodic built-in self-test (BIST) schemes are already commercialized for memories and for random logic. The paper at hand extends this approach to interconnect structures. A BIST scheme is presented which targets interconnect defects before they will actually affect the system functionality at nominal speed. A BIST schedule is developed which significantly reduces aging caused by electromigration during the lifetime application of the periodic test.
Keywords: Electrical and Electronic Engineering

EM-Aware Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Broadband optical Ta2O5 antennas for directional emission of light - Farheen, Henna; Yan, Lok-Yee; Quiring, Viktor; Eigner, Christof; Zentgraf, Thomas; Linden, Stefan; Förstner, Jens; Myroshnychenko, Viktor (Optics Express)
Highly directive antennas with the ability of shaping radiation patterns in desired directions are essential for efficient on-chip optical communication with reduced cross talk. In this paper, we design and optimize three distinct broadband traveling-wave tantalum pentoxide antennas exhibiting highly directional characteristics. Our antennas contain a director and reflector deposited on a glass substrate, which are excited by a dipole emitter placed in the feed gap between the two elements. Full-wave simulations in conjunction with global optimization provide structures with an enhanced linear directivity as high as 119 radiating in the substrate. The high directivity is a result of the interplay between two dominant TE modes and the leaky modes present in the antenna director. Furthermore, these low-loss dielectric antennas exhibit a near-unity radiation efficiency at the operational wavelength of 780 nm and maintain a broad bandwidth. Our numerical results are in good agreement with experimental measurements from the optimized antennas fabricated using a two-step electron-beam lithography, revealing the highly directive nature of our structures. We envision that our antenna designs can be conveniently adapted to other dielectric materials and prove instrumental for inter-chip optical communications and other on-chip applications.
Keywords: tet_topic_opticalantenna

Negative polarization of light at backscattering from a numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Icarus)
We model negative polarization, which is observed for planetary regoliths at backscattering, solving a full wave problem of light scattering with a numerically exact Discontinuous Galerkin Time Domain (DGTD) method. Pieces of layers with the bulk packing density of particles close to 0.5 are used. The model particles are highly absorbing and have irregular shapes and sizes larger than the wavelength of light. This represents a realistic analog of low-albedo planetary regoliths. Our simulations confirm coherent backscattering mechanism of the origin of negative polarization. We show that angular profiles of polarization are stabilized if the number of particles in a layer piece becomes larger than ten. This allows application of our approach to the negative polarization modeling for planetary regoliths.
Keywords: tet_topic_scattering

Concept Study of an LLC Converter with Magnetically Resonant Inductor - Böcker, Joachim (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Identification of piezoelectric material parameters using optimised multi-electrode specimens - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

Long-Term Memory Recursive Least Squares Online Identification of Highly Utilized Permanent Magnet Synchronous Motors for Finite-Control-Set Model Predictive Control - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

Detection of Defects on Irregularly Structured Surfaces using Supervised and Semi-Supervised Learning Methods - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneiß, Volker; Hedayat, Christian; Kuhn, Harald (2022 Smart Systems Integration (SSI))
In the manufacture of real wood products, defects can quickly occur during the production process. To quickly sort out these defects, a system is needed that finds damage in the irregularly structured surfaces of the product. The difficulty in this task is that each surface is visually different and no standard defects can be defined. Thus, damage detection using correlation does not work, so this paper will test different machine learning methods. To evaluate different machine learning methods, a data set is needed. For this reason, the available samples were recorded manually using a static fixed camera. Subsequently, the images were divided into sub-images, which resulted in a relatively small data set. Next, a convolutional neural network (CNN) was constructed to classify the images. However, this approach did not lead to a generalized solution, so the dataset was hashed using the a- and pHash. These hash values were then trained with a fully supervised system that will later serve as a reference model, in the semi-supervised learning procedures. To improve the supervised model and not have to label every data point, semi-supervised learning methods are used in the following. For this purpose, the CEAL method (wrapper method) is considered in the first and then the Π-Model (intrinsically semi-supervised).
Keywords: Machine Learning; CNN; Hashing; semi-supervised learning

Differentiation of an SBFE model in the context of material parameter determination - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Birk, Carolin; Henning, Bernd

Estimation of piezoelectric material parameters of ring-shaped specimens - Friesen, Olga; Claes, Leander; Feldmann, Nadine; Henning, Bernd

An Initialization Scheme for Meeting Separation with Spatial Mixture Models - Boeddeker, Christoph; Cord-Landwehr, Tobias; von Neumann, Thilo; Haeb-Umbach, Reinhold (Interspeech 2022)

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Secure learning-based MPC via garbled circuit - Tjell, Katrine; Schluter, Nils; Binfet, Philipp; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Encrypted dynamic control with unlimited operating time via FIR filters - Schluter, Nils; Neuhaus, Matthias; Schulze Darup, Moritz (2021 European Control Conference (ECC))

Tailored neural networks for learning optimal value functions in MPC - Teichrib, Dieter; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Behavioral Economics for Human-in-the-Loop Control Systems Design: Overconfidence and the Hot Hand Fallacy - Protte, Marius; Fahr, Rene; Quevedo, Daniel E. (IEEE Control Systems)
Keywords: Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering; Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering

Reconfigurable and real-time high-bandwidth Nyquist signal detection with low-bandwidth in silicon photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Meier, Janosch; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Optics Express)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain detection of a high-bandwidth Nyquist signal with a low-bandwidth silicon photonics Mach-Zehnder modulator based receiver. As the Nyquist signal has a rectangular bandwidth, it can be multiplexed in the wavelength domain without any guardband as a part of a Nyquist-WDM superchannel. These superchannels can be additionally multiplexed in space and polarization. Thus, the presented demonstration can open a new possibility for the detection of multidimensional parallel data signals with silicon photonics. No external pulse source is needed for the receiver, and frequency-time coherence is used to sample the incoming Nyquist signal with orthogonal sinc-shaped Nyquist pulse sequences. All parameters are completely tunable in the electrical domain. The feasibility of the scheme is demonstrated through a proof-of-concept experiment over the entire C-band (1530 nm–1560 nm), employing a 24 Gbaud Nyquist QPSK signal due to experimental constraints on the transmitter side electronics. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can process Nyquist signals of 90 GHz optical bandwidth, suggesting a possibility to detect symbol rates up to 90 GBd in an integrated Nyquist receiver.

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Analysis of the effect of jitter and non-idealities on photonic digital-to-analog converters based on Nyquist pulses - Singh, Karanveer; Kress, Christian; Mandalawi, Younus; Misra, Arijit; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Emulation of integrated high-bandwidth photonic AWG using low-speed electronics - Singh, Karanveer; Meier, Janosch; Kress, Christian; Misra, Arijit; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Next-Generation Optical Communication: Components, Sub-Systems, and Systems XI)

Wideband SiN pulse interleaver for optically-enabled analog-to-digital conversion: a device-to-system analysis with cyclic equalization - Zazzi, Andrea; Müller, Juliana; Ghannam, Ibrahim; Battermann, Moritz; Rajeswari, Gayatri Vasudevan; Weizel, Maxim; Scheytt, J. Christoph; Witzens, Jeremy (Optics Express)
We present the design and experimental characterization of a silicon nitride pulse interleaver based on coupled resonator optical waveguide filters. In order to achieve a targeted free spectral range of 1.44 THz, which is large given the reduced optical confinement of the silicon nitride platform, individual ring resonators are designed with tapered waveguides. Its application to time-interleaved photonically-assisted ADCs is analyzed by combining experimental characterization of the photonic integrated circuit with a comprehensive model of the entire ADC. The impact of fundamental signal distortion and noise sources affecting the converter is investigated and suitable equalization techniques at the digital signal processing level are evaluated. The novel application of a simple but powerful equalization filter in the DSP domain allows for a significant improvement of the digitized signal SNR. An ENOB of 5 over a 75 GHz bandwidth (150 GS/s) and an ENOB of 4.3 over a 100 GHz bandwidth (200 GS/s) are expected to be achievable with compact and off-the-shelf single-section semiconductor mode locked lasers, that can be further improved with lower noise light sources.

Light Scattering by Large Densely Packed Clusters of Particles - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Springer Series in Light Scattering - Volume 8: Light Polarization and Multiple Scattering in Turbid Media)
We review our results of numerical simulations of light scattering from different systems of densely packed irregular particles. We consider spherical clusters, thick layers and monolayers with realistic topologies and dimensions much larger than the wavelength of light. The maximum bulk packing density of clusters is 0.5. A numerically exact solution of the electromagnetic problem is obtained using the Discontinuous Galerkin Time Domain method and with application of high- performance computing. We show that high packing density causes light localization in such structures which makes an impact on the opposition phenomena: backscattering intensity surge and negative linear polarization feature. Diffuse multiple scattering is significantly reduced in the case of non-absorbing particles and near-field interaction results in a percolation-like light transport determined by the topology of the medium. With this the negative polarization feature caused by single scattering gets enhanced if compared to lower density samples. We also confirm coherent double scattering mechanism of negative polarization for light scattered from dense absorbing slabs. In this case convergent result for the scattering angle polarization dependency at backscattering can be obtained for a layer of just a few tens of particles if they are larger than the wavelength.
Keywords: tet_topic_scattering

Von der Präsenz-Blockveranstaltung zum Blended Learning-Konzept - Graefe, Grit; Temmen, Katrin (Hochschullehre erforschen)

Noise Processes and Nonlinear Mechanisms in Optoelectronic Phase-Locked Loop Using a Balanced Optical Microwave Phase Detector - Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)

One-bit target detection in collocated MIMO radar and performance degradation analysis - Xiao, Yu-Hang; Ramirez, David; Schreier, Peter J; Qian, Cheng; Huang, Lei (IEEE Transactions on Vehicular Technology)

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Chapter III – Using Energy More Efficiently. Preparing the Ground with Energy Efficiency. - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Chapter III – Using Energy More Efficiently. Saving Energy in Industry and Commerce. - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas)

Techno-economic Potential of High-Temperature Heat Pump Integration - Schlosser, Florian; Walmsley, Timothy; Kong, Lana; Zühlsdorf, Benjamin; Meschede, Henning

Two-Sided Endless Optical Polarization Control with 2 x 100 krad/s Tracking Speed - Noé, Reinhold; Koch, Benjamin (Photonic Networks; 23th ITG-Symposium)

An Open-Source Transistor Database and Toolbox as a Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (2022 IEEE Applied Power Electronics Conference and Exposition (APEC))

An Open-Source FEM Magnetics Toolbox for Power Electronic Magnetic Components - Förster, Nikolas; Piepenbrock, Till; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2022; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)